Going for gold: Sports and exercise groups for people with dementia and carers contribute to their well-being - Chadwick, Claire; Hussain, Aisha; Carone, Laura; Yates, Jen; Dening, Tom (Frontiers in Rehabilitation Sciences, 2022)
Background Interventions involving exercise appear to have positive effects, both for people with dementia and for their carers. Quality of life and well-being are especially important outcomes. This study investigated how a sports and exercise group for people with dementia and their carers could contribute to the well-being of those attending the group. Methods The study was a qualitative investigation, comprising semi-structured interviews, a focus group and observations. Participants included people with dementia and carers attending the group sessions, as well as staff providing the programme. The group sessions were provided weekly by the charitable trust of a leading sports venue. Data were analysed using thematic analysis. Results A total of 16 participants were interviewed, including four people with dementia, eight carers, and four members of staff. Five main themes were identified: ‘Support to keep active and engaged is highly valued by people with dementia and carers’; ‘The challenges of being a carer are significant but sharing the experience really helps’; ‘People with dementia can have flourishing social lives’; ‘The group helps to maintain identity despite physical and role changes’; and ‘There are practical aspects of the group that make it appealing’. Discussion People with dementia enjoy physical activity and experience the benefits of it. The sports and exercise group had an important role in providing access to activities that people with dementia and their carers value and enjoy, but would be difficult to undertake without a facilitated and safe environment. The group benefited the well-being of both people with dementia and carers in various ways, with peer support being of particular importance for carers.